Germany's labour market in coronavirus distress - New challenges to safeguarding employment - Alexander Herzog-Stein; Patrick Nüß; Lennert Peede; Ulrike Stein (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2021)
We analyse measures of internal flexibility taken to safeguard employment during the Coronavirus Crisis in comparison to the Great Recession. Cyclical working-time reductions are again a major factor in safeguarding employment. Whereas during the Great Recession all working-time instruments contributed to the reduction in working time, short-time work now accounts for almost all of the working-time reduction. Short-time work was more rapidly extended, more generous, and for the first time a stronger focus was put on securing household income on a broad basis. Still, the current crisis is more severe and affects additional sectors of the economy where low-wage earners are affected more frequently by short-time work and suffered on average relatively greater earnings losses. A hypothetical average short-time worker had a relative income loss in April 2020 that was more than twice as large as that in May 2009. Furthermore, marginal employment is affected strongly but not protected by short-time work.
Keywords: E24; E32; J08; J20; 330; Epidemie; Coronavirus; Arbeitsmarkt; Arbeitsmarktpolitik; Deutschland